Translation Problems of Phraseological Units with a Color Component and Recommendations Regarding It - Makhsetova, Zuhra Torebayevna; ugli, Usmanov Azizjon Zakirjon; ugli, Yunsov Asadbek Shuhrat (International Journal on Integrated Education, 2023)
This article covers the translation problems of phraseological units with a color component and recommendations about it.